Effect of Service Quality on Consumer Satisfaction: A Study on Traditional Retail (Nanostore) in Kabupaten Subang - Mulyadi, Mulyadi; Tiorida, Ermina (Universitas Diponegoro, 2024)
The development of modern retail in Indonesia is so fast, this has an impact on the growth and development of various retailers in various regions. Nanostore as a micro business which is one of the traditional retailers which in Indonesia is known as a grocery shop is a business run by families in villages that support the daily needs of the surrounding community. In 2022 there will be 326 modern retailers which will result in competition leading to higher consumer expectations for service quality. That way, the purpose of this study is to determine the quality of services provided by nanostore owners, to determine the effect of service quality on nanostore consumer satisfaction in Subang Regency. Data collection was carried out by distributing questionnaires using a Likert scale to 230 nanostore respondents. The sampling method used purposive sampling technique. The research method used is descriptive quantitative method with correlation analysis techniques, simple regression analysis, coefficient of determination, and hypothesis testing. The results have shown that service quality affects customer satisfaction by 46.6%.